Mutational analysis of an RNA recognition element that mediates localization of bicoid mRNA. - Macdonald, P.M.; Kerr, K. (Molecular and Cellular Biology, 1998)
Localization signals are RNA regulatory elements that direct the localization of mRNAs to subcellular sites. Localization signals presumably function by mediating RNA recognition events through which the mRNA becomes associated with the localization machinery. At present little is known about individual RNA recognition events, which in turn has limited progress in identifying the trans-acting binding factors involved in these events. Here we describe a detailed characterization of the RNA elements required for the RNA recognition event, event A, that initiates localization of bicoid mRNA in the Drosophila ovary. One element is a helix in which nucleotide identities are not important, suggesting that it plays a primarily structural role. Immediately adjacent to the helix is a recognition domain in which the identities of some, but not all, nucleotides are important for function. Comparison of two related but different RNAs that both support recognition event A further defines the important features of the recognition domain.